TRANSAKSI E-COMMERCE: ANALISIS SUDUT PANDANG AKAD WAKALAH DAN SALAM SERTA PSAK SYARIAH 103 - Pekerti, Retno Dyah; Susilowati, Dewi; Herwiyanti, Eliada (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2019)
The online purchasing and selling transaction reviewed in Islamic perspective is the category of muamalah in the field of trade or business. The rise of online transactions often causes problems. Sellers and buyers in online transactions have not understood the terms and conditions in buying and selling so that often occurs gharar, and do not know how the contract should be done. This research is to explore and analyze akad salam and application of  PSAK Syariah 103 for online transactions. This research uses qualitative method with case study research conducted in Tasikmalaya City by using in-depth interview technique. Informants in the study consisted of business people, consumers, ustadz jurists, Majelis Ulama Indonesia (MUI) Tasikmalaya City, and academics. The results showed that the rukun and terms of sale and purchase in the perspective of sharia only known in general. Akad salam and PSAK Syariah 103 not known by the seller or buyer. Accounting of Salam can be applied to any sale and purchase transactions with the provisions of the scheme and recording, recognition, measurement, and presentation must be in accordance with the rules in PSAK Syariah 103. This research can be a reference for academics and become input for regulators, businessmen and community.